A real-world analysis of pharmacotherapy adherence and the factors influencing it in Serbia: a nationwide, population-based, cross-sectional study - Srebro, Dragana; Bukumirić, Zoran; Šantrić Milićević, Milena (Frontiers in Public Health, 2024)
Introduction Monitoring the pharmacotherapy adherence in society is crucial for identifying occurance and causes of potential inadequate use of drugs and inform providers about the need for better customer counceling. It is necessary component of the strategic planning of the quality of healthcare services. This population- based study aimed to assess the medication intake adherence in the Republic of Serbia and the individual factors and health system variables influencing its pattern. Methods We applied a cross-sectional approach to study medication intake adherence using a secondary analysis of the latest 2019 Serbian National Health Survey data. The statistical modeling of the pharmacotherapy adherence incorporated sociodemographic data, self-reported disease, and lifestyle behavior. Results In 2019, in the representative sample of 12,066 adults in Serbia, requiring prescribed medicine, 49.8% did comply with the prescribed drugs, and 50.2% do not. Participants who adhered to prescribed medication were significantly (p < 0.001) older (62.4 ± 14 years), predominantly female (55.3%), had secondary education (48.5%), resided in southern and eastern parts of Serbia (55.5%), and belonged to the lowest income quintile (21.4%). The participants most often take prescribed drugs for hypertension (64.1%) and lower back pain (30.5%), while around 20% take medication for coronary disease, diabetes mellitus, and high blood cholesterol. About 85–92% of participants with financial or general difficulties using prescribed medication. Conclusion There is poor medication intake adherence to prescribed medication in Serbia. Gender, age, and region determine the adherence. Also, health-related and healthcare system-related factors impact the use of prescribed medication. Study findings can inform planning the counceling interventions in the target groups where improving medication adherence is necessary, as well as to enhance training of healthcare providers about pharmacotherapy adherence.